A new prognostic strategy for gastric carcinoma: albumin level and metastatic lymph node ratio - AKÇAKAYA, ADEM; IŞIK, ADEM; Okan, I.; Firat, D.; YILMAZ, BERZA; Akcakaya, ADEM; Sahin, M. (My University, 2014)
Aim. We evaluated the prognostic significance of preoperative serum albumin value and metastatic lymph node ratio for gastric cancer patients.